Fighting COVID-19 in the West Africa after experiencing the Ebola epidemic - Pourya Gholizadeh; Moussa Sanogo; Amadou Oumarou; Maad Nasser Mohamed; Yacouba Cissoko; Mamadou Saliou Sow; Pasquale Pagliano; Patassi Akouda; Sid'Ahmed Soufiane; Akory Ag Iknane; Mamadou Oury; Safiatou Diallo; et al. (Tabriz University of Medical Sciences, 2021)
Coronavirus disease 2019 (COVID-19) dissemination occurred from December 2019 and quickly spread to all countries. Infected patients with COVID-19 have had a wide range of symptoms, ranging from mild to severe illness. The most mortality was observed in patients with underlying disease and over 45 years. World statistics have shown that the COVID-19 outbreak is most expanded in Middle Eastern, West Asian, European, North, and South American countries, and is least expanded in African countries. Therefore, the aim of the paper was the evaluation of six African countries including Mali, Mauritania, Niger, Guinea, Togo, and Djibouti to find why this disease is least expanded in African countries. Study was conducted by Questioner for countries health organizers to define their different aspect exposure and fight with COVID-19 including epidemiology, clinical aspects of the disease, case definitions, diagnosis laboratory confirmation, and referral of cases by the portal of entry, case management, and disease prevention in these countries. According to this opinion review, due to the low international flights and low domestic travel, the spread, and prevalence of COVID-19 was low and the return of the immigrants of these countries has caused the spread of COVID-19 among these countries. Experience, preparation, and impact of previous infections epidemic such as the Ebola virus epidemic would have beneficial, which have promoted certain reflexes among people that cause low dissemination in these countries.